A igualdade formal ante a desigualdade material na relação de emprego doméstico no Brasil - Andrade Júnior, Marcelo Oliveira Serrano de (2014)
The work is about the formal equality before the material inequality on the domestic labour relation. Although the domestic employees are entitled of minimally fundamental rights to a worthy life, the constant human rights violations reveals that the conquest of equality still appears distant regarding the acknowledgment and respect from the society towards this segment. But why is so hard to secure the rights of the domestic employees? On a search to comprehend such fact, the research starts from the premise that the domestic employee is devalued for being a conflict point for class, gender and race discrimination, and also not considered a profit generating activity. This discrimination that affects the domestic labour is due to a historical, social and legal construction, therefore, firstly, the social and historical contexts regarding the emergence of the domestic class is analyzed, as well as the legal posture adopted referring the job, including the international level, trough the analysis of the 189th Convention from the International Labour Organization. Promptly, the work brings the conception for the equality principle and demonstrates, trough a gender perspective, that the domestic labour is much discriminated due to social residue from slavery and patriarchate, besides being an easy target for the capitalist exploitation. Beyond this, registers the peculiarity of the domestic labour not relying on a supervision system due the home inviolability principle, as well as the difficulty of producing proof on an eventual court litigation. At last, the study confronts the present scenario of the domestic labour in Brazil with the principles of human dignity, citizenship and the social value of work; and analyzes how the instruments from the affirmative actions are being used by the State on the combat agains inequality of this labour relation. The research concludes that the acknowledgment of ratified rights when confronting the inequalities have not produced any effects, as this occupation is widely socially devalued. This way, the implementation of actions aiming to promote a decent work for this category is indispensable, consisting on an important tool to include these historically excluded individuals. For this research there were used, essentially, the historical and bibliographic methods. The pertinence for this study advent from the rising debate around the legal regulation of the domestic employees which involves thousand of women.